CALDAS-COULTHARD , C. R. News associal practice: a study in critical discourse analysis. Florianópolis: Editora da UFSC, 1997, 114 p. - Moura, Augusto (Cadernos de Linguagem e Sociedade, 2010)
CALDAS-COULTHARD , C. R. News associal practice: a study in critical discourse analysis. Florianópolis: Editora da UFSC, 1997, 114 p.